Overexpression of Smac is associated with the development of primary Sjogren's syndrome. Issue 7 (July 2019) - Kang, Yuanyuan; Zhang, Ying
Abstract : Background: Primary Sjögren's syndrome (pSS) is a systemic autoimmune disease characterized by keratoconjunctivitis sicca, xerostomia, and extraglandular abnormalities. The precise etiology remains unclear. Previous studies have revealed that the apoptosis played an important role in the pSS. Herein, we investigated the expression and effect of second mitochondria-derived activator of caspase (Smac) in patients with pSS and associated the expression with clinicopathological parameters. Methods: Smac expression was checked in labial salivary glands of surgical specimens from cases of pSS using immunohistochemistry, reverse transcription-quantitative PCR, and Western blot. The results of immunohistochemistry were analyzed for clinicopathological parameters. In addition, the content of Smac in cytoplasm and mitochondria were examined. Results: The mRNA of Smac, the content of Smac in cytoplasm, the Smac protein in the pSS patients increased significantly compared with the healthy controls ( p < 0.05). The content of Smac in mitochondria decreased significantly compared with the healthy controls ( p < 0.05). The integral optical density of Smac protein levels were positively correlated with IgG (r = 0.7435, p < 0.05) and erythrocyte sedimentation rate (ESR) (r = 0.7925, p < 0.05). Conclusion: Smac plays an important role in the development of pSS.